2015
DOI: 10.1016/j.seizure.2015.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormones: Possible roles in epilepsy pathology

Abstract: Thyroid hormones (THs) L-thyroxine and L-triiodothyronine, primarily known as metabolism regulators, are tyrosine-derived hormones produced by the thyroid gland. They play an essential role in normal central nervous system development and physiological function. By binding to nuclear receptors and modulating gene expression, THs influence neuronal migration, differentiation, myelination, synaptogenesis and neurogenesis in developing and adult brains. Any uncorrected THs supply deficiency in early life may resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 144 publications
(166 reference statements)
1
49
0
11
Order By: Relevance
“…Conversely, for the mood stabilizer lamotrigine, FDA labeling lists hypothyroidism as rare (<1 in 1000 patients) (49), and recent reviews found little to no evidence for an effect of lamotrigine on thyroid hormones (50,51). Despite the overlapping characteristics, and shared pharmacology of BD and epilepsy (52-55), we could only find literature on carbamazepine and oxcarbazepine associated with hypothyroidism in epilepsy, a disease in which the pathogenesis may involve thyroid hormones (56). Evidence from epilepsy studies shows adverse thyroid effects from valproate (51,(57)(58)(59), carbamazepine (51,57,59), and oxcarbazepine (51,59).…”
Section: Discussionmentioning
confidence: 97%
“…Conversely, for the mood stabilizer lamotrigine, FDA labeling lists hypothyroidism as rare (<1 in 1000 patients) (49), and recent reviews found little to no evidence for an effect of lamotrigine on thyroid hormones (50,51). Despite the overlapping characteristics, and shared pharmacology of BD and epilepsy (52-55), we could only find literature on carbamazepine and oxcarbazepine associated with hypothyroidism in epilepsy, a disease in which the pathogenesis may involve thyroid hormones (56). Evidence from epilepsy studies shows adverse thyroid effects from valproate (51,(57)(58)(59), carbamazepine (51,57,59), and oxcarbazepine (51,59).…”
Section: Discussionmentioning
confidence: 97%
“…Enhanced level of thyroid hormones increased oxidative state in tissues where the metabolic rates are higher. Particularly, the fact that they increase lipid per-oxidation, decrease antioxidant enzymatic activities and decrease gamma-aminobutyric acid synthesis in the brain may be a trigger for migraine (21,22). On the other hand, inadequate thyroid function results in slower metabolism, which in turn causes the body to retain fluid and mucin glycoprotein as a result of inappropriate secretion of antidiuretic hormone and this process eventually causes vasodilatation and swelling of brain tissue, which can result in cerebral hyperactivity causing migraine (23).…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid hormones are important for maintaining carbohydrate and lipid metabolism, cell growth and development. 6,7 Hypothyroidism even in subclinical hypothyroidism form has been associated with an increased risk of coronary heart disease. 8 The prevalence of AED induced thyroid dysfunction and the long term consequences remain uncertain mainly due to routine thyroid functions tests are not performed in the clinic.…”
Section: Introductionmentioning
confidence: 99%